Stereoselective hydrostannation of substituted alkynes initiated by triethylborane and reactivity of bulky triorganotin hydrides - Faraoni, María Belén (2006)
This paper reports the results obtained in a study on the radical hydrostannation of mono- and disubstituted alkynes with bulky triorganotin hydrides using triethylborane as initiator. The addition of trineophyl- (1), tris[(phenyldimethylsilyl)methyl]- (2), and 9-tripticyldimethyltin (3) hydride to eight alkynes was carried out at room temperature leading to vinylstannanes in good to excellent yields and, mostly, with complete stereoselectivity. The results obtained in a study on the relative reactivity of trineophyl- (1), tris[(phenyldimethylsilyl)methyl]- (2), 9-triptycyldimethyltin (3) hydrides, and tri-n-butyltin hydride (29) using the radical reactions between these hydrides and 6-bromo-1-hexene (28) are also reported. Full 1H-, 13C-, and 119Sn NMR characteristics are included.